2016
DOI: 10.20360/g2xw2k
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Explicit Pronunciation Instruction on Undergraduate EFL Learners' Vowel Perception

Abstract: Since English pronunciation errors by Persian speakers are often caused by the transfer of the Persian language sound system, the present study investigated the effect of explicit pronunciation instruction on undergraduate English as a Foreign Language (EFL) learners' vowel perception enhancement. The nonequivalent group, pretest-posttest design was employed to study two classes of English literature and English teaching students at Kosar University of Bojnord (KUB) as the experimental group (EG) and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…As reported by Ghorbani (2011), Ghorbani, Neissari andKargozari (2016) and Ghorbani and Neissari (2015), pronunciation is rarely taught and tested in the Iranian educational system mainly because of the washback impact of the tests. Other reported reasons for this negligence include lack of time, teachers' low proficiency, lack of phonetic transcription in the available material, and the assumption that learning accurate pronunciation is possible only through listening to native speakers.…”
Section: Discussionmentioning
confidence: 98%
“…As reported by Ghorbani (2011), Ghorbani, Neissari andKargozari (2016) and Ghorbani and Neissari (2015), pronunciation is rarely taught and tested in the Iranian educational system mainly because of the washback impact of the tests. Other reported reasons for this negligence include lack of time, teachers' low proficiency, lack of phonetic transcription in the available material, and the assumption that learning accurate pronunciation is possible only through listening to native speakers.…”
Section: Discussionmentioning
confidence: 98%
“…Positive effects of explicit teaching of pronunciation are also reported by Ghorbani et al (2016). They enabled EFL learners to identify and notice their specific pronunciation errors and then the learners investigated the impact of explicit pronunciation instruction on their vowel perception.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Recently, several researchers have explored the efficacy of explicit pronunciation instruction on learners' development (e.g. Couper, 2003Couper, , 2006Ghorbani, Neissari, & Kargozari, 2016;Saito, 2007Saito, , 2011Saito, , 2012. They agree that clear instruction of pronunciation is essential in language classrooms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Shamiri and Farvardin (2016) conducted interviews with 70 English as a Foreign Language (EFL) students and found that most of them prefer their errors to be corrected implicitly. However, the majority of studies comparing the effects of implicit and explicit instruction on the pronunciation and listening comprehension of learners of English shows that explicit teaching methods are more effective than implicit methods (Gorbani, Neissari, & Kargozari, 2016; Gordon, Darcy, & Ewert, 2013; Khaghaninejad & Maleki, 2015; Khanbeiki & Abdolmanafi‐Rokni, 2015).…”
Section: Implicit and Explicit Instructionmentioning
confidence: 99%